PENGELOLAAN APBDES UNTUK MENINGKATAKAN PENDAPATAN MASYARAKAT DESA - Imaningtyas, Elsa (Journal of Development Economic and Social Studies, 2022)
This study aims to determine the type of management of the Village Revenue and Expenditure Budget (APBDes) to increase the income of the people of Blabakan Village, Mejayan District, Madiun Regency and find out the impact of managing the Village Revenue and Expenditure Budget (APBDes) to increase the income of the people of Blabakan Village. The method used  this research quantitative with a descriptive approach. Data obtained by means interviews (direct interviews with informants and indirect interviews with respondents using questionnaires) and documentation. The results of  study indicate that the type APBDes management increasing community income village of Blabakan in the field village development and community empowerment. The program activities are physical infrastructure development activities, agricultural training, livestock/agriculture assistance,. The consequence of the existence of APBDes management in increasing people's income is seen when the community participates through programs/activities that exist in the APBDes where with this participation the community's income has increased. This then becomes the basis consideration in order to shift the priority the APBDes allocation in the field of community empowerment. With program activities on community empowerment, it is hoped that community income can increase. Therefore, this research expected to able  provide  reference in improving village government.